2013
DOI: 10.1016/j.biochi.2012.09.022
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulation of GLUT1 activity in human corneal limbal epithelial cells and fibroblasts

Abstract: The corneal epithelial tissue is a layer of rapidly growing cells that are highly glycolytic and express GLUT1 as the major glucose transporter. It has been shown that GLUT1 in L929 fibroblast cells and other cell lines can be acutely activated by a variety agents.However, the acute regulation of glucose uptake in corneal cells has not been systematically investigated. Therefore, we examined glucose uptake in an immortalized human corneal–limbal epithelial (HCLE) cell line and compared it to glucose uptake in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 40 publications
1
17
0
Order By: Relevance
“…2, indicate that curcumin inhibits 2DG uptake in a dose dependent manner with a maximum of 84% inhibition at 70–100 μM with an IC 50 = 19 μM. We confirmed this inhibitory effect of curcumin in HCLE and HK2 cells, two other cell lines where GLUT1 is the primary transporter responsible for 2DG uptake [32,33]. The effects of a submax (25 μM) and maximum (75 μM) effective concentrations of curcumin were measured and reported on Table 1.…”
Section: Resultssupporting
confidence: 61%
“…2, indicate that curcumin inhibits 2DG uptake in a dose dependent manner with a maximum of 84% inhibition at 70–100 μM with an IC 50 = 19 μM. We confirmed this inhibitory effect of curcumin in HCLE and HK2 cells, two other cell lines where GLUT1 is the primary transporter responsible for 2DG uptake [32,33]. The effects of a submax (25 μM) and maximum (75 μM) effective concentrations of curcumin were measured and reported on Table 1.…”
Section: Resultssupporting
confidence: 61%
“…The enhanced uptake was caused by an increase expression combined with an activation of the transporter. It was observed that compounds which activated glucose uptake in L929 cells either had no effect in HCLE cell, or in the case of thiol reactive compounds, actually inhibited glucose uptake [30]. If GLUT1 in HCLE cells is already activated by involvement of the key thiols, we hypothesized that alkaline conditions would not further activate glucose uptake.…”
Section: Resultsmentioning
confidence: 97%
“…Previous work has shown that HCLE cells express GLUT1 as the primary glucose transporter and have much higher glucose uptake rates than L929 cells [30]. The enhanced uptake was caused by an increase expression combined with an activation of the transporter.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results argue against such a mechanism because 1) they suggest that the drop in OXPHOS-mediated ATP production is fully compensated for by increased glycolytic activity, and 2) they demonstrate that total cellular ATP amount is not significantly reduced in cells treated with OXPHOS inhibitors for 24 h. Glut1 activity might also be increased by a mechanism involving AMP-activated protein kinase, activation (phosphorylation) of which was linked to stimulation of Biophysical Journal 109 (7) 1372-1386 GLC transport during OXPHOS inhibition (9,67). Alternatively, Glut1 redox modification and oligomerization were demonstrated to regulate Glut1 activity (68)(69)(70)(71) and the amount of active Glut1 at the PM might be increased by stimulation of Glut1 translocation from internal storage vesicles to the PM or by activation of PM-localized Glut1 by OXPHOS inhibition (9)(10)(11)13).…”
Section: Oxphos Inhibition Stimulates Cellular Glc Uptakementioning
confidence: 99%